Peace and goodwill? Using an experimental game to analyse the Desarrollo y Paz initiative in Colombia - Orazio Attanasio; Luca Pellerano; David Phillips (Institute for Fiscal Studies (IFS), 2009)
Several decades of conflict, rebellion and unrest severely weakened civil society in parts of Colombia. Desarollo y Paz is the umbrella term used to describe the set of locally-led initiatives that aim at addressing this problem through initiatives to promote sustainable economic development and community cohesion and action. In this paper we analyse the findings from a series of 'public good' games that were conducted between November 2005 and February 2007 in 104 municipalities in rural and urban Colombia with mainly poor participants. The data covers municipalities both with ('treatment') and without ('control') a PRDP in place, and within the 'treatment' municipalities, both beneficiaries and non beneficiaries of the PRDP initiative. The data for 'control' municipalities was collected as part of the evaluation of Familias en Accion (FeA), Colombia's conditional cash transfer programme.The game is structured as a typical free-rider problem with the act of contributing to the 'public good' (a collective money pot) being always dominated by non-contribution. We interpret contribution as an act consistent with a high degree of social capital.Potentially endogenous selection into the programme makes identifying programme effects difficult but we find strong and suggestive evidence that exposure to PRDPs improve social capital and that this extends beyond direct beneficiaries of the programme. In particular, the duration of programme operation and the proportion of programme beneficiaries in a game session increase contribution to the public good, suggesting that in order to have a major impact the programme must be sufficiently 'intensive'.
Keywords: C93; I38; D74; H41; 330; Social Capital; Conflict; Experimental Games; Public Goods; Evaluation Methods; Bürgerkrieg; Innere Sicherheit; Öffentliches Gut; Trittbrettfahrerverhalten; Social Capital; Kolumbien